Sejarah Perkembangan Ilmu Di Dunia Barat Dan Islam Abad: Kuno, Tengah, Moderen, & Kontemporer - Muhammad Anas Kamaluddin; Usman (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study analyzes the development of science in the Western and Islamic worlds through four historical periods: ancient, medieval, modern, and contemporary. This study uses a literature study method with a descriptive analysis approach, collecting data from books, journals, and previous research. The analysis includes data reduction, data presentation, and conclusions. In the Western world, the ancient period is marked by Greek natural philosophy, the Middle Ages by the dominance of religion and scholasticism, the modern century by the Renaissance and the paradigm of secularism, materialism, positivism, and hedonism, and the contemporary century by a critical cross-disciplinary approach. In the Islamic world, the ancient period was the heyday of science with significant contributions in medicine, chemistry, and algebra. The medieval period declined due to internal and external conflicts, while the modern period was marked by the revival and reform of Islam through the thoughts of figures such as Sayyed Jamaluddin Al-Afghani, Muhammad Abduh, and Rasyid Ridha. In the contemporary period, thinkers such as Muhammad Arkoun and Muhammad Iqbal integrated modern social science approaches and Islamic-Western education.